Pemberdayaan Petani melalui Produksi dan Aplikasi Biofarm Urin Kambing sebagai Pupuk Organik Cair untuk Meningkatkan Produktivitas Tanaman : Pengabdian - Soekamto, Mira Herawati; Budiarti, Marlinda Indah Eka; Tabara, Reijeng; Sangadji, Ismail Munadi (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
Empowering farmers to increase their knowledge and skills in using organic fertilizers is an important part of realizing a sustainable agricultural system. In Klaru sub-district, the use of urine as POC is still very low, even though the raw material is abundant. The main obstacles found were the lack of knowledge about the fermentation process, storage and application of POC, as well as the high dependence on chemical fertilizers. This community service program aims to increase the capacity of farmers in utilizing goat urine waste as raw material for making liquid organic fertilizer (Biofarm) as an alternative to chemical fertilizers. Activities include outreach, Biofarm production training, fermentation assistance, and application to plants. The training was attended by 15 farmers and resulted in increased knowledge and skills. The goat urine biofarm empowerment program has been proven to be very effective because it is able to increase farmer understanding from 40% to 85%, satisfaction from 55% to 90%, production capacity from 35% to 80%, and interest in continuing from 50% to 90%. This program has successfully improved farmers' knowledge, skills, and attitudes toward liquid organic fertilizer technology made from goat urine. In addition to providing agronomic benefits, this activity also increases cost efficiency, reduces dependence on chemical fertilizers, and strengthens farmer group collaboration in waste management and organic technology development.